POTENSI PEMANFAATAN TUMBUHAN PAKU Diplazium esculentum Swartz (Studi Kasus) Di DISTRIK AIFAT UTARA KABUPATEN MAYBRAT PROVINSI PAPUA BARAT - Margaretha ., Turot; Bobby ., Polii; Hengki D. Walangitan (Sam Ratulangi University, 2016)
This study aims to measure the productivity of potential utilization of ferns Diplazium esculentum Swartz and analyze the socio-economic characteristics of community members who employed fern Diplazium esculentum Swartz as a source of income and to describe the pattern of utilization and contribution of ferns Diplazium esculentum Swartz for the community members in Kampung Ayawasi, District North Aifat, District of Maybrat, West Papua Province. The method used is the method of lines; census method is less than 100. This study includes ecological aspects, economic aspects i.e. incomes. Other analytical method used is the analysis of the contribution to household income communities. This study found that productivity of potential utilization of ferns Diplazium esculentum Swartz of Village community in Ayawasi Aifat is total revenue of Rp 530 000,00 or (68.86%) in a range of categories is quite effective at 25-75. Income people who use the fern Diplazium esculentum Swartz can be influenced by socio-economic factors are factors respondents' personal characteristics such as age, education and land, as well as how to harvest. The utilization pattern of fern Diplazium esculentum Swartz has contributed to an increase in household income communities. It was proven that members of community who are active in picking, earn greater revenue compared to people who are not actively lower revenue in conducting harvesting ferns.